The Existence and Contribution of Sufism in Resolving Religious Conflicts - Efendi, Efendi; Putri, Endrika Widdia; Amril, Amril; Gazali, Gazali (Islam Transformatif : Journal of Islamic Studies, 2023)
Abstract This article aims to explore the existence of sufism and its contribution to resolving religious conflicts. As part of Islamic science, sufism is an esoteric dimension of Islamic teachings that discusses aspects of spirituality. In this context, sufism is used as an approach to achieve peace of mind for its followers. This article uses qualitative methods and literature studies.Datas are collected from various books and other scientific articles analyzed using exploratory, interpretive, and analytical methods. The research results show that the history of the development of sufism has always experienced dynamics and ups and downs. Differences in views always accompany its development between those who recognize and reject sufism as an Islamic science. The struggle between Sunni and Falsafi Sufism cannot be avoided. However, this is not a real problem because the main problem is not the material differences of Sunni and Falsafi Sufism, but rather the political, power, economic, and social intrigue accompanying it. Despite this arrangement, sufism continues to exist to this day and has given rise to the latest developments such as perennial sufism. Perennial sufism is an approach used in sufism to build harmony among humans. In this context, the perennial approach in sufism can be used to resolve religious conflicts. In other words, perennial sufism has contributed as an approach to reducing religious conflict in the modern era with the spirit of religion and the values of tolerance contained in it.Â Artikel ini bertujuan untuk mengeksplorasi eksistensi tasawuf dan konstribusinya bagi penyelesaian konflik keagamaan. Sebagai bagian dari ilmu keislaman, tasawuf merupakan dimensi esoteris ajaran Islam yang membahas aspek spritualitas. Dalam konteks ini, tasawuf dijadikan sebagai pendekatan untuk meraih ketenangan jiwa pengikutnya. Artikel ini menggunakan metode kualitatif dan studi kepustakaan, sehingga data-data bersumber dari berbagai buku dan artikel-artikel ilmiah lainnya yang dianalisis dengan metode eksploratif, interpretatif dan analitis. Hasil penelitian menunjukkan bahwa sejarah perkembangan tasawuf selalu mengalami dinamika dan pasang surut. Perbedaan pandangan senantiasa mengiringi perkembangannya antara yang mengakui serta menolak tasawuf sebagai keilmuan Islam. Pergulatan antara tasawuf sunni dan falsafi tidak dapat dihindarkan. Hal demikian bukan masalah, karena permasalahan pokok bukan pada materi tasawuf sunni dan falsafi, melainkan intrik politik, kekuasaan, ekonomi dan sosial yang mengiringinya. Terlepas dari pengaturan itu, tasawuf tetap eksis hingga hari ini dan memunculkan perkembangan terbaru seperti tasawuf perenial. Tasawuf perenial adalah sebuah pendekatan yang digunakan dalam tasawuf untuk membangun harmonisasi sesama manusia. Dalam konteks ini pendekatan perenial dalam tasawuf dapat dijadikan sebagai bentuk penyelesaian konflik keagamaan. Dengan kata lain, tasawuf perenial memiliki kontribusi sebagai salah satu pendekatan dalam meredakan konflik keagamaan pada era modern dengan spirit agama dan nilai- nilai-nilai toleransi yang terkandung padanya.